A NIR‐II Fluorescent Probe for Hydrogen Sulfide Detection Based on Blocking Intramolecular Charge Transfer. Issue 12 (21st March 2023) - Zhao, Shuai; Xue, Yonggan; Hu, Lijuan; Sun, Fang; Nie, Jun; Chang, Yincheng
Abstract: A NIR‐II fluorescent probe (Et‐1080) for H2 S detection was fabricated based on the intramolecular charge transfer blocking mechanism. The enhanced electron density of the indole donor further drove the Et‐1080′s absorption and emission to the NIR‐II region with a high molar absorption coefficient and acceptable fluorescence quantum yield. The C=N double bond of electron‐deficient indole can react with H2 S rapidly via a nucleophilic addition mechanism, resulting in the destruction of conjugated structure and fluorescence quenching of the Et‐1080 molecule. The probe showed high selectivity and sensitivity to H2 S, which could realize the rapid detection of H2 S in NIR‐II band and showed great potential in the further disease diagnosis associated with H2 S. Abstract : A NIR‐II fluorescent probe for H2 S detection was fabricated based on the intramolecular charge transfer blocking mechanism. The probe showed high selectivity and sensitivity to H2 S, which could realize the rapid detection of H2 S in NIR‐II band and showed great potential in the further disease diagnosis associated with H2 S.